Teknik Penentuan Populasi dan Sampel dalam Penelitian Pendidikan - Rangga Gustiawan Nazara (Lembaga Pengembangan Kinerja Dosen, 2026)
The quality of educational research is strongly influenced by the accuracy in defining the research population and selecting appropriate sampling procedures. Proper determination of population and sample is essential to ensure that research findings are valid and can be generalized to a broader context. However, many educational studies still provide limited and unsystematic explanations regarding how populations are defined, how samples are selected, and how sample sizes are determined in the research design. This lack of methodological clarity may reduce the credibility and reliability of research results. This study aims to examine the concepts of population and sample, various sampling techniques, and their implications for improving the quality of educational research. The study employed a literature review approach by synthesizing scientific articles and methodological references published within the last ten years that discuss population and sampling in educational research. The results of the review indicate that clearly defining the research population, including both target and accessible populations, is a fundamental step in designing a study. Furthermore, the use of appropriate sampling techniques, such as simple random sampling, stratified sampling, and cluster sampling, plays an important role in obtaining representative samples. Determining an adequate sample size and implementing systematic sampling procedures can also reduce potential research bias and enhance data validity. Therefore, accurate population identification and appropriate sampling design are essential factors in strengthening the reliability and generalizability of educational research findings.